The Importance of Red Cell Distribution width value in Obstructive Sleep Apnea - Sagmen, Seda Beyhan; Parmaksız, Elif Torun; Kiral, Nesrin; Salepci, Banu; Comert, Sevda (Eastern Journal of Medical Sciences, 2019)
Background: Obstructive sleep apnea (OSA) is a very common condition among sleep disorders. The relationship between inflammation and OSA has been described and inflammation was found to have a role in the development of the disease. Hematologic parameters have been found as inflammatory biomarkers in various diseases. Aim: To evaluated the association of OSA and red blood cell distribution width (RDW) value, and the association of RDW value in OSA patients with hypertension (HT) and without HT. Method: A retrospective and cross-sectional evaluation of the complete records of 412 patients, who were presented to our sleep center and underwent polysomnography. Polysomnographic parameters and RDW-CV values for these patients were evaluated. Result: Total 372 patients with obstructive sleep apnea syndrome and 40 people as a control group were included in the study. There was no significant difference between the OSA and control group regarding the mean RDW value (p>0.05). No statistically significant association was detected between RDW and apnea hypopnea index (AHI) in the evaluation of the OSA group. There was a negatively significant correlation between RDW and minimum oxygen saturation and mean oxygen saturation values in the OSA patients (p=0.002; r=-0.159,p=0.004, r=-0.148;respectively). A statistically significant difference was found in the mean RDW value based on the presence of HT in all OSA groups (p=0.031). The mean RDW of the group with HT was higher than group without HT. Conclusion: RDW must be taken into consideration during follow-up in severe OSA, and in the presence of HT.